2018
DOI: 10.11152/mu-1604
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in musculoskeletal ultrasound in pediatric rheumatology?

Abstract: Musculoskeletal ultrasound (MSUS) has become almost indispensable in the rheumatology settings nowadays, allowing early diagnosis, careful guidance during procedures such as joint injections and therapy monitoring. Nonetheless, the applicability of MSUS in pediatric population is still limited. Recently, a standardized MSUS examination procedure in pediatric patients with rheumatic diseases, definitions for synovitis and the sonographic features of joints in healthy children has been developed. Also, important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The MSUS features of indicator joint in different subtypes of JIA Effusion, synovial hypertrophy, and enthesopathy are main MSUS features of involved joints of JIA [14,23]. Figure 3 summarized the presence of above 3 features in joints of different subtypes.…”
Section: Disease Activity and Physical Function Scoresmentioning
confidence: 98%
“…The MSUS features of indicator joint in different subtypes of JIA Effusion, synovial hypertrophy, and enthesopathy are main MSUS features of involved joints of JIA [14,23]. Figure 3 summarized the presence of above 3 features in joints of different subtypes.…”
Section: Disease Activity and Physical Function Scoresmentioning
confidence: 98%
“…Although US-detected subclinical synovitis has not been determined as a predictor of flares in a recent study, 8 increased rate of flare has been reported in patients in clinical remission but presenting positive Doppler findings. 9 Thus early initial diagnosis and also detection of disease activity are crucial for achieving treatment response and reducing the sequelae. Since we have excluded patients with severe contractures, diagnostic accuracy of SWE for differentiation of JIA disease has failed to reach statistically significant levels.…”
Section: Discussionmentioning
confidence: 99%
“…Early initial diagnosis and early detection of disease activity are crucial for achieving treatment response and reducing the disease sequelae [ 30 ]. Remission status is more accurately diagnosed by US than clinical examination; however, the prognostic value of subclinical synovitis is still being defined [ 12 , 32 , 33 ]. These issues became even more challenging given SMI sensitivity.…”
Section: Update In Ultrasoundmentioning
confidence: 99%